Environmental diversity and stable isotope variation in faunas: Implications for human diet reconstruction in Argentine mid-latitude deserts - Otaola, Clara (2018)
This paper presents the results of an isotopic study of δ13C and δ15N values for bone collagen from 209 modern faunas from central-western Argentina. The samples come from two ecologically distinct areas: the Monte and Patagonian Deserts. The results confirm high intra- and inter-taxonomic variation in both isotopes. Previous studies of camelids, rodents and ostrich eggshells in this region showed a clear relation between animal δ13C and δ15N values, altitude, and the percentage of C3 and C4 plants. This pattern was not fully met among the species considered in this paper. No statistical differences were seen between δ13C values from Monte and Patagonian Deserts, although differences in δ15N were found. When samples from saltmarsh contexts were considered separately, differences among δ15N isotopic values become more pronounced, pointing to a relation between δ15N isotopic signatures and soil salinity. Archaeological human diet reconstruction based on isotopic data needs to pay attention to this significant variation in resources isotopic patterns in order to be used as a reliable dietary indicator.